Ionic strength and temperature dependence of rheological behavior of deep-water sedimental slurries. (1st December 2022) - Hu, Shijun; Chen, Pan; Wang, Yong; Wei, Changfu; Li, Pengchun
Abstract: Understanding the rheological behavior of deep-water sedimental slurries is important for assessing the interaction between the deep-water sediment and pipelines. A series of sedimentation and rheological tests have been conducted on the deep-water slurries from the South China Sea, and the ionic strength and temperature dependence of its rheological behavior is investigated. It is shown the ionic strength can significantly influence the yield stress of the slurry through changing its fabric. A critical mass fraction is identified to distinguish the suspension state and contact state in the soil-water system. With a mass fraction less than the critical mass fraction, the slurry is in suspension state, and its yield stress and dynamic moduli increase as temperature increases. With a higher mass fraction, however, the slurry is in contact state, and its yield stress and dynamic moduli decrease with increasing temperature. A theoretical model for the yield stress of the slurries is introduced based on the DLVO theory. The model describes very well the yield stress characteristics of the slurries in the suspension state. The effect of electrostatic repulsive forces on the yield stress is dominant in the suspension state; in the contact state, however, the effect of attractive forces becomes significant. Highlights: The effects of ionic strength and temperature on the rheological behavior of deep-water slurries are characterized. A critical mass fraction is identified to distinguish the slurries into the suspension state and contact state. It is shown that the rheological behavior of the slurries depends on their dispersive states.